Content and balance of trace elements in placenta on different stages of gestation - I. I. Shkolna; I. V. Tarasova; V. V. Markevych; V. O. Petrashenko; M. P. Zagorodnii; O. V. Hordienko (Zaporožskij Medicinskij Žurnal)
Functional status of placenta, which provides nutrients to the fetus, plays an important role in miscarriage.